Atmospheric freeze drying of garlic slices based on freezing point depression - Xu, Duan; Wenchao, Liu; Guangyue, Ren; Xiaotong, Yang; Yunhong, Liu (International Journal of Agricultural and Biological Engineering, 2015)
Garlic is difficult to dry due to browning reaction and degradation of heat-sensitive component. Freeze drying (FD) can keep good shape, color and nutrition of dried garlic, but it consumes long drying time and high energy. To shorten drying time and obtain high quality products, atmospheric freeze drying (AFD) was developed for drying garlic slices. The effects of different inlet air temperature programs on product quality and drying process were studied during AFD process. It was found that freeze point depression could lead to part of ice thawing resulting in product quality deterioration when the air temperature was not low enough. Based on this, a step-down-up temperature program was developed to reduce the drying time and provide good product quality. Keywords: garlic, freeze drying, atmospheric freeze drying DOI: 10.3965/j.ijabe.20150804.1933 Citation: Duan X, Liu W C, Ren G Y, Yang X T, Liu Y H. Atmospheric freeze drying of garlic slices based on freezing point depression. Int J Agric & Biol Eng, 2015; 8(4): 133－139.